Answer:
![f(x)=5(x-2)^{2}+6](https://tex.z-dn.net/?f=f%28x%29%3D5%28x-2%29%5E%7B2%7D%2B6)
Step-by-step explanation:
we have
![f(x)=5x^{2} -20x+26](https://tex.z-dn.net/?f=f%28x%29%3D5x%5E%7B2%7D%20-20x%2B26)
This is the equation of a vertical parabola open upward
The vertex is a minimum
The equation of a vertical parabola in vertex form is equal to
![f(x)=a(x-h)^2+k](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-h%29%5E2%2Bk)
where
(h,k) is the vertex
Convert the given function to vertex form
Factor the leading coefficient
![f(x)=5(x^{2} -4x)+26](https://tex.z-dn.net/?f=f%28x%29%3D5%28x%5E%7B2%7D%20-4x%29%2B26)
Complete the square
![f(x)=5(x^{2} -4x+4)+26-20](https://tex.z-dn.net/?f=f%28x%29%3D5%28x%5E%7B2%7D%20-4x%2B4%29%2B26-20)
![f(x)=5(x^{2} -4x+4)+6](https://tex.z-dn.net/?f=f%28x%29%3D5%28x%5E%7B2%7D%20-4x%2B4%29%2B6)
Rewrite as perfect squares
------> equation in vertex form
The vertex is the point (2,6)
The correct answer is d. Please give me brainlest I hope this helps let me know if it’s correct or not okay
Answer:
circle b and it is bigger by 1 centimeter
Step-by-step explanation:
since circle b has a radius of 5 and radius is have of the diameter you have to do 5+5 to get the diameter when you do that you get 10 and then you have to subtract circle a diameter which is 9 from circle b diameter which is 10 so 10-9 is 1
Answer: y=2
Step-by-step explanation:
Distribute the numbers -2 and 3...
6y-2y-2=3y-6+6
The -6 and 6 cancel each other out...
6y-2y-2=3y
Combine like terms....
4y-2=3y
Move 4y over....
-2=-y
Multiply both sides by -1.....
2=y
That’s your solution! Hope this helps!
Answer:
![b=\sqrt{c^2-a^2}](https://tex.z-dn.net/?f=b%3D%5Csqrt%7Bc%5E2-a%5E2%7D)
Step-by-step explanation:
The given relation is
![c=\sqrt{a^2+b^2}](https://tex.z-dn.net/?f=c%3D%5Csqrt%7Ba%5E2%2Bb%5E2%7D)
To make
the subject, we square both sides of the equation to get;
![c^2=(\sqrt{a^2+b^2})^2](https://tex.z-dn.net/?f=c%5E2%3D%28%5Csqrt%7Ba%5E2%2Bb%5E2%7D%29%5E2)
![c^2=a^2+b^2](https://tex.z-dn.net/?f=c%5E2%3Da%5E2%2Bb%5E2)
Isolate
on one side of the equation;
![c^2-a^2=b^2](https://tex.z-dn.net/?f=c%5E2-a%5E2%3Db%5E2)
Or
![b^2=c^2-a^2](https://tex.z-dn.net/?f=b%5E2%3Dc%5E2-a%5E2)
We take the positive square root of both sides to get;
![b=\sqrt{c^2-a^2}](https://tex.z-dn.net/?f=b%3D%5Csqrt%7Bc%5E2-a%5E2%7D)